1996
DOI: 10.1080/01652176.1996.9694615
|View full text |Cite
|
Sign up to set email alerts
|

Detection of oestrus in dairy cows: A new approach to an old problem

Abstract: SUMMARYFertility indices, such as non-return rate and number of services per conception, have worsened significantly over the past few years. Because oestrus detection is one of the major factors influencing these indices, this study was performed to determine whether, how long, and at what time dairy cows show signs of oestrus in their behaviour. Two high producing herds with about 40 open cows were observed for 30 minutes every 2 hours for 6 weeks. The various signs of oestrus were recorded. The milk progest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
4
8

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 10 publications
5
93
4
8
Order By: Relevance
“…Therefore, both farmers and researchers have paid much attention to decreased fertility in dairy cows [17,77,97]. Impaired fertility has a multifactorial background.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, both farmers and researchers have paid much attention to decreased fertility in dairy cows [17,77,97]. Impaired fertility has a multifactorial background.…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous works (Van Eerdenburg et al, 1996;Kerbrat and Disenhaus, 2004), we assumed that oestrus expression and detection were highly correlated in our database. Therefore, we adjusted oestrus detection data to estimate oestrus expression.…”
Section: Description Of the Modelmentioning
confidence: 52%
“…Several studies with modern high producing dairy cows indicate a relatively strong positive relationship between the oestradiol blood concentration during the late follicular phase and the duration and intensity of behavioural oestrus. For instance, Lyimo et al (2000) (Table 2) found a significant correlation (r = 0.56; P = 0.023) between the maximum oestradiol concentration during the oestrous phase of the cycle and the total oestrus score as measured using the scoring method of Van Eerdenburg et al (1996). In the same study, the correlation of maximum oestradiol level with the length of the oestrous period was not significant (r = 0.45; P = 0.081).…”
Section: Ovarian Steroid Hormones and Oestrous Behaviour Expression Imentioning
confidence: 89%
“…The intensity of oestrus is often expressed as a cumulative score for weighted behavioural signs. The scoring method proposed by Van Eerdenburg et al (1996), shown in Table 1, has been frequently used. The intensity of oestrous behaviour expression is not only important for successful artificial insemination but also for high conception and calving rates once inseminated.…”
Section: Introductionmentioning
confidence: 99%